Bone hyperalgesia after mechanical impact stimulation: A human experimental pain model - Finocchietti, Sara; Graven-Nielsen, Thomas; Arendt-Nielsen, Lars (Somatosensory & motor research, 2014)
Abstract Hyperalgesia in different musculoskeletal structures including bones is a major clinical problem. An experimental bone hyperalgesia model was developed in the present study. Hyperalgesia was induced by three different weights impacted on the shinbone in 16 healthy male and female subjects. The mechanical impact pain threshold (IPT) was measured as the height from which three weights (165, 330, and 660 g) should be dropped to elicit pain at the shinbone. Temporal summation of pain to repeated impact stimuli was assessed. All these stimuli caused bone hyperalgesia. The pressure pain threshold (PPT) was assessed by a computerized pressure algometer using two different probes (1.0 and 0.5 cm2). All parameters were recorded before (0), 24, 72, and 96 h after the initial stimulations. The IPTs were lowest 24 h after hyperalgesia induction for all three weights and the effect lasted up to 72 h (p < 0.05). The PPT obtained with the 1.0 cm2 probe was significantly lower than the PPT obtained with the 0.5 cm2 probe, regardless of the time. Females developed more pronounced hyperalgesia reflected in reduced IPTs and PPTs (p < 0.05). Temporal summation was significantly (p < 0.05) facilitated after induction of hyperalgesia with the strongest facilitation in males. The developed bone pain and hyperalgesia model may provide the basis for studying this fundamental mechanism of bone-related hyperalgesia and be used for profiling compounds developed for this target.